2015
DOI: 10.1089/cyber.2015.0265
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Videogames as Complementary Therapeutic Tool for Cognitive Behavioral Therapy in Bulimia Nervosa Patients

Abstract: Although cognitive behavioral therapy (CBT) has been demonstrated to be the most effective approach for the treatment of bulimia nervosa (BN), there is lack of studies showing whether a combination with a serious video game (SVG) might be useful to enhance patients' emotional regulation capacities and general outcome. The aims of this study were (a) to analyze whether outpatient CBT + SVG, when compared with outpatient CBT - SVG, shows better short-term outcome; (b) to examine whether the CBT + SVG group is mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 51 publications
1
42
1
Order By: Relevance
“…As illustrated in Figure 2, the system’s interaction with the patient follows a gamification approach (56) where progress is measured in scores/rewards and the patient is encouraged to progress in her/his exposure treatment. The gamification approach will be partly based on previous work where techniques for visualization of rewards and progress were employed to motivate eating disorder patients (5759). …”
Section: Proposed Solutionmentioning
confidence: 99%
“…As illustrated in Figure 2, the system’s interaction with the patient follows a gamification approach (56) where progress is measured in scores/rewards and the patient is encouraged to progress in her/his exposure treatment. The gamification approach will be partly based on previous work where techniques for visualization of rewards and progress were employed to motivate eating disorder patients (5759). …”
Section: Proposed Solutionmentioning
confidence: 99%
“…So far, serious games have not often been investigated in combination with CBT. A study in bulimia patients and a study in patients with a severe gambling disorder have shown better therapeutic outcomes when CBT interventions are complemented with serious gaming than in the case of a standalone CBT intervention [20, 21]. Thus, serious games may be a promising add-on to CBT, as an innovative tool to motivate users to increase their knowledge and skills regarding health-related behavior.…”
Section: Introductionmentioning
confidence: 99%
“…However, only 40% to 50% of BN and BED patients recover from binge eating at the end of a CBT course [2,3] and interventions recently developed do not improve much binge frequency when they complement CBT [4,5]. This partial efficacy could stem from the fact that CBT and these interventions neglect the processes occurring specifically during binges.…”
Section: Introductionmentioning
confidence: 99%